FEATURES OF STATE REGULATION OF FOREIGN TRADE RELATIONS IN THE AGRO-FOOD COMPLEX OF RUSSIA - Reshetnikova, Natalia (Revista Inclusiones, 2020)
The article deals with issues of interstate regulation of foreign trade at the bilateral, regional, and global levels, as well as studies the institutional forms of this issue. The purpose of the research was a comprehensive study of the state regulation issues of foreign trade relations in the agro-food complex. The article considers features of the main strategies of state policy in relation to foreign trade, namely, protectionism and liberalism. Forms of protectionism, such as selective, sectoral, collective, hidden, and neo-protectionism are identified and analyzed. Two areas of export policy have been studied. In the first case, the priority is given to exports and foreign trade development in relation to the domestic economy. In the second case, foreign trade and exports are considered a resource for the development and modernization of the domestic economy. The article analyzes the world experience in the export relations and features of the World Trade Organization’s (WTO) requirements for Russia’s export policy.